MULTI MEDIA INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN MENGENALKAN BENDA PADA ANAK AUTI - Merti Megawaty (JURNAL AKADEMIKA)
Flowers Nations Foundation Autism is one of the schools that have not developed the computer media in the learning process, so that the need for the use of new media learning better in delivering learning, in this case the use of the system used is animated multimedia-based learning media. The use of multimedia in the llearning process will use vidio animation, sound, and multimedia objects to the introduction described in the form of images.